Aerobic-Strength Exercise Improves Metabolism and Clinical State in Parkinson’s Disease Patients - Krumpolec, Patrik; Vallova, Silvia; Slobodova, Lucia; Tirpakova, Veronika; Vajda, Matej; Schon, Martin; Klepochova, Radka; Janakova, Zuzana; Straka, Igor; Sutovsky, Stanislav; Turcani, Peter; Cvecka, Jan; et al. (Frontiers in Neurology, 2017)
Regular exercise ameliorates motor symptoms in Parkinson`s disease (PD). Here, we aimed to provide evidence that exercise brings additional benefits to the whole-body metabolism and skeletal muscle molecular and functional characteristics, which might help to explain exercise-induced improvements in the clinical state. Three-months supervised endurance/strength training was performed in early/mid-stage PD patients and age/gender-matched individuals (n=11/11). The effects of exercise on resting energy expenditure (REE), glucose metabolism, adiposity, and muscle energy metabolism (31P-MRS) were evaluated and compared to non-exercising PD patients. Two muscle biopsies were taken to determine intervention-induced changes in fiber type, mitochondrial content, and expression of genes related to muscle energy metabolism, as well as proliferative and regenerative capacity. Exercise improved the clinical disability score (MDS-UPDRS), bradykinesia, balance, walking speed, REE, and glucose metabolism and increased muscle expression of energy sensors (AMPK). However, the exercise-induced increase in muscle mass/strength, mitochondrial content, type IIa fiber size, and post-exercise phosphocreatine recovery (31P-MRS) were found only in controls. Nevertheless, MDS-UPDRS was associated with muscle AMPK and mechano-growth factor (MGF) expression. Improvements in fasting glycemia were positively associated with muscle function and the expression of Sirt1 and Cox7a1, and the parameters of fitness/strength were positively associated with the expression of MyHC2, MyHC7, and MGF. Moreover, reduced bradykinesia was associated with better muscle metabolism (maximal oxidative capacity and post-exercise phosphocreatine recovery; 31P-MRS). Exercise training improved the clinical state in early/mid-stage Parkinson’s disease patients, including motor functions and whole-body metabolism. Although the adaptive response to exercise in PD was different from that of controls, exercise-induced improvements in the PD clinical state were associated with specific adaptive changes in muscle functional, metabolic, and molecular characteristics. This study was registered at clinicalTrials.gov (NCT02253732).